Gelation mechanism and tribological performances of two-component cholesterol-based supramolecular gel lubricant. (March 2021) - Zhang, Jiaying; Bao, Luyao; Yu, Qiangliang; Ma, Zhengfeng; Dong, Rui; Zhang, Chaoyang; Bai, Yanyan; Cai, Meirong; Zhou, Feng; Liu, Weimin
Abstract: A novel and simple method for the preparation of two-component gel lubricant and some evaluation of its physicochemical and lubricating properties are reported. The addition of two-component gelator including bis(2-ethylhexyl) sulfosuccinate and cholesterol to white oil can result in self-assembly to form a gel. The gelation mechanism was characterized by the combination of atomistic molecular dynamics simulation and experiment. It not only has excellent thermal stability, but also possesses thermal reversibility, creep recovery and thixotropic properties. Noticeably, the gel can significantly enhance lubricous and AW performances of base oil. Obtained by FIB-TEM, EDS, XPS and QCM characterization, we speculate that the gelator forms an effective adsorption and tribochemical reaction film, so it can protect the contact surface from being worn. Graphical abstract: Image 1 Highlights: The manuscript reports a novel, simple and low cost method for the preparation of two-component gel lubricant. The AOT and cholesterol added to food grade white oil can result in self-assembly to form a gel. The obtained gel lubricants have excellent lubricity, wear resistance and higher load carrying capacity. The gel lubricants are green and non-toxic, provide potential application in the field of food or drug processing.